Income Inequality as a Canadian Cohort Ages: An Analysis of the Later Life Course - Steven G. Prus (Luxembourg Income Study (LIS), 2000)
Survey of Consumer Finances cross-sectional data from 1973 to 1996 are used in this article to examine Canadian trends in income inequality over the middle and later stages of the life course of a synthetic cohort born between 1922 and 1926. Using Gini coefficients, the findings show that income inequality decreases within a cohort as it grows old; that is, the Canadian retirement income system levels the distribution of income in later life. The observed decrease in inequality corresponds with a decrease in income from earnings and an increase in dependency on state benefits. The progressive nature of public pension programs in Canada increases the relative income share and the average income of the poorest seniors. Moreover, cross-national comparisons of income inequality show that Canada exhibits a more equal distribution of income in old age compared to countries with similar old-age welfare systems, such as the United States.
Keywords: 330; Haushaltseinkommen; Einkommensverteilung; Kanada; Alternde Bevölkerung